Controversies in clinical management of postmenopausal osteoporosis - Sotelo, Wendy (2016)
Osteoporosis is the most common bone disease in the globalized world, with high impact on health care costs due to progressive increase in life expectancy and the existence of new diagnostic procedures. Bone fractures are the main consequence of this disease, which cause chronic pain, disability and loss of quality of life, and can even lead to death. Existing international clinical guidelines based on evidence from randomized trials give standards for the treatment of osteoporosis, especially its post- menopausal form, offering both pharmacological and non-pharmacological actions. Based on results from follow-up studies in a large number of patients, we currently discuss aspects of traditional therapeutic support, such as the use and dosage of calcium supplements. It is proposed that there may exist an apparent non-benefit from its intake among those with an adequate level of dietary calcium; it is possible that some of them may develop adverse events such as chronic constipation, diverticulitis, kidney stones or cardiovascular disease. Similarly, some studies suggest to use biphosphonates for a limited period of time, which associates with loss of efficiency and the possibility of adverse events, such as atypical femoral fractures and osteonecrosis of the jaw bone. This last adverse event is also described with the use of denosumab. What is more, among those who receive teriperatide there exists the infrequent possibility of developing neoplasms such as osteosarcoma, so that the recommendation is that its use cannot exceed 2 years. Finally, as a result of research on serum concentrations of vitamin D and their relationship with signs and symptoms that may present in its deficiency, as well as the possible benefits from vitamin D on autoimmunity, some neoplasms and a mild improvement in bone mass, we can affirm that the supplementation with vitamin D3 must be an important part in its therapy.